2017
DOI: 10.2174/1389450118666170711150034
|View full text |Cite
|
Sign up to set email alerts
|

Cell Wall Associated Factors of Mycobacterium tuberculosis as Major Virulence Determinants: Current Perspectives in Drugs Discovery and Design

Abstract: Studies demonstrated that the cell wall components are unique in terms of their contribution in mycobacterium pathogenesis. Targeting these can hamper the growth of M. tuberculosis. In this study, we scrutinize the drugs under trials and the potential candidates screened through in silico findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Lipid profiling studies showed increase in total lipid and TDM content in rv1288 expressing M. smegmatis strain. Virulent M.tb strains are usually rich in TDM (Singh et al, 2017). Similarly the expression of mycolyl transferase Ag85A protein in M. smegmatis resulted in increase concentration of the glycolipids TDM and TMM in the cell (Elamin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Lipid profiling studies showed increase in total lipid and TDM content in rv1288 expressing M. smegmatis strain. Virulent M.tb strains are usually rich in TDM (Singh et al, 2017). Similarly the expression of mycolyl transferase Ag85A protein in M. smegmatis resulted in increase concentration of the glycolipids TDM and TMM in the cell (Elamin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Most of bacteria have a protective outer shell (cell wall), and Mab's low permeability cell wall plays a vital role in their intrinsic resistance 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Most of bacteria have a protective outer shell (cell wall), and Mab’s low permeability cell wall plays a vital role in their intrinsic resistance 25 . Arabinosyltransferase C, a protein involved in cell wall synthesis, is encoded by the embC gene, and the impairment of cell wall synthesis caused by the loss of embC increases the permeability of the cell wall in Mab, making the bacteria more sensitive to antibiotics 19, 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Plasma membrane also contains lipoglycans, phospholipids including phosphatidylinositol mannosides, and other glycolipids [11]. Antigen 85 complex proteins, porins, putative transporters, and mammalian cell entry protein family were mostly found in mycobacterial cell wall fraction that contains mycolic acid esterifying arabinogalactan constituting the inner leaflet of mycomembrane, along with glycolipids, phospholipids, lipoglycans, and proteins [12].…”
Section: Components Of Mycobacterial Cell Wallmentioning
confidence: 99%